Tracking UK Freelance Workforce Trends 1992-2014 - Kitching, Kitching (Senate Hall, 2015)
Using data from the UK Labour Force Survey, the paper describes the major trends in freelance workforce numbers during the past 20 years. Operationalising a definition of freelancing in terms of Labour Force Survey categories, the data indicate both a substantial absolute increase in freelancer numbers and growth as a proportion of all workforce jobs. Possible explanations for the increase are discussed, paying particular attention to the demand for freelancers. Although a number of studies suggest a shift towards the adoption of flexible labour strategies, the evidence base on the forces underlying the expansion of freelance working is limited and fragmented. Research questions seeking to explore the trends in greater detail are identified. Keywords: freelance workers, regulation, organisational restructuring, flexible labour strategies, occupational structure, Labour Force Survey
Keywords: freelance workers|regulation|organisational restructuring|flexible labour strategies|occupational structure|Labour Force Survey